2014
DOI: 10.5430/ijfr.v5n3p176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Financial Crisis on the Islamic Banks Profitability - Evidence from GCC

Abstract: Using pooled data for 24 Islamic banks operating in Bahrain, Kuwait, Qatar, Saudi Arabia and UAE over the 2005-2012 period the current study examines empirically the impact of the global financial crisis on the Islamic banks' profitability.The study finds that the financial crisis does not have significant impact on Islamic banks profitability. Favorable macro-economic conditions, bank size and equity capital are important factors in increasing Islamic banks' profitability. Furthermore Increasing owners' equit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…Panel (A) presents the pooled model, while panel (B) presents the Seemingly Unrelated Regression (SUR) (or Zellner method) 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panel (A) presents the pooled model, while panel (B) presents the Seemingly Unrelated Regression (SUR) (or Zellner method) 4 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the effect clearly differs significantly between the two banking forms. Almanaseer (2014) analyzes the effects of the 2008 subprime crisis on the GCC Islamic banks. He reached the conclusion of no effect of the crisis on the profitability of the GCC Islamic banks due to the profit sharing systems mechanism, which allows Islamic banks to keep their net worth and avoid deterioration under difficult economic situation.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…We also find several studies that examine the impact of GDP growth on Islamic banks' behaviour. For instance, Bashir (2003), Hassan and Bashir (2003), Zeitun (2012) and Almanaseer (2014) documented that a favourable macroeconomic environment stimulates higher profitability of Islamic banks. Masood and Ashraf (2012) showed that the loan losses provision of Islamic banks is lower than that of conventional banks, and GDP growth contributes negatively to the bank's profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact size of the banks and equity capital increases the profitability of the Islamic banks and because of increase in the equity capital, expenses of the Islamic bank's decreases and profitability of the Islamic bank's increases [14]. [15] checked the impact of the financial crises at the both banking streams of Islamic and conventional of Qatar's banks and found that Islamic banks management of assets, deposits is better than the conventional banks and Islamic banks were less liquid than the conventional.…”
Section: Literature Reviewmentioning
confidence: 99%